Precision Medicine Needs to Think Outside the Box - Martschenko, Daphne O.; Young, Jennifer L. (Frontiers in Genetics, 2022)
Precision medicine offers a precious opportunity to change clinical practice and disrupt medicine’s reliance on crude racial, ethnic, or ancestral categories by focusing on an individual’s unique genetic, environmental, and lifestyle characteristics. However, precision medicine and the genomic studies that are its cornerstone have thus far failed to account for human diversity. This failure is made clearer when looking at individuals who encapsulate a mosaic of different genetic ancestries and do not fit neatly into existing population labels. This piece argues that precision medicine continues to rely on the same forms of crude categorization it seeks to unsettle. Until the scientific community creates inclusive solutions for individuals who fall outside or between our existing population labels, precision medicine will continue to fall short in its aims.